Scott Family Enterprises : building the path to effective governance - Ward, John L., (SAGE Knowledge. Cases., 2018)
Risk managers have more tools than ever to help protect their companies from risk. Complex financial instruments, intricate mathematical models, and access to massive amounts of data can help the risk manager structure a multifaceted strategy to decrease volatility and protect the company from a catastrophic event. However, these tools have their own risks that can complicate a risk manager's job. Analyzing corn price volatility helps students understand four best practices for risk managers, regardless of the specific risks they face or the strategies they employ: quantify the company's exposure; understand the nature of the risk; understand how the hedge works in practice; and separate hedging and speculation.